Europeanizing education : governing a new policy space - Lawn, Martin [Verfasser]; Grek, Sotiria [Verfasser] (Symposium Books, 2012)
"The study of common and diverse effects in the field of education across Europe is a growing field of inquiry and research. It is the result of many actions, networks and programmes over the last few decades and the development of common European education policies. 'Europeanizing Education' describes the origins of European education policy, as it metamorphosed from cultural policy to networking support and into a space of comparison and data. The authors look at the early development and growth of research networks and agencies, and international and national collaborations. The gradual increase in the velocity and scope of education policy, practice and instruments across Europe is at the heart of the book." (Verlag, BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; S 4.3 Steuerung; L 6.3.1 Diagnose- & Messinstrumente; I 2.2 Europa; EU-Bildungspolitik; Europäischer Bildungsraum; Historische Entwicklung; Bildungssteuerung; Internationale Zusammenarbeit; Bildungsmonitoring; OECD; Kompetenzfeststellung; Leistungsvergleich; Selbstevaluation; Europäische Union; 1970-2010